Two-dimensional copper carbide electrode material and lithium storage performance calculation method thereof

By using two-dimensional copper carbide as the negative electrode material of lithium-ion batteries and using first principles to calculate lithium storage performance, the problems of low active site density per unit mass and slow ion diffusion speed are solved, and battery performance with high energy density and high power output are achieved.

CN119905584APending Publication Date: 2025-04-29GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510194255.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material graphite has a low unit mass active site density, which is difficult to meet the demand for high energy density, and the ion diffusion speed is slow, which limits its performance in high power output occasions.

Method used

Two-dimensional copper carbide is used as the negative electrode material of lithium-ion batteries, and its structural optimization and lithium storage performance calculation methods are obtained through first-principles calculations, including derive infrastructure, structural optimization, energy band diagram calculation, phonon spectrum analysis, lithium ion adsorption calculation and diffusion path search.

Benefits of technology

Two-dimensional copper carbonized electrode materials have high structural stability and conductivity. The migration barrier of lithium ions on their surface is low, the charging and discharge speeds are fast, and the theoretical specific capacity is as high as 770.7mA h/g, which is far better than graphite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905584A_ABST
    Figure CN119905584A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium battery electrode materials, and particularly discloses a two-dimensional copper carbide electrode material and a lithium storage performance calculation method thereof.The two-dimensional copper carbide electrode material comprises a C atomic layer located in the middle and Cu atomic layers located on the two sides of the C atomic layer, the C atomic layer is connected with the two Cu atomic layers through a Cu-C-Cu bond; a first principle calculation result shows that the two-dimensional copper carbide electrode material not only has excellent structural stability and conductivity, but also can effectively adsorb lithium ions, the migration barrier of the lithium ions on the surface of the two-dimensional copper carbide electrode material is only 0.075 eV, and the conductivity of the two-dimensional copper carbide electrode material is greatly improved. The low potential barrier value indicates that the two-dimensional copper carbide electrode material disclosed by the invention has extremely high charging and discharging speeds in the battery; besides, the theoretical specific capacity of the two-dimensional copper carbide electrode material disclosed by the invention is as high as 770.7 mAh / g, which is far better than 372 mAh / g of graphite, so that the excellent performance of the two-dimensional copper carbide electrode material disclosed by the invention as the electrode material of the lithium ion battery is further proved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium battery electrode materials, and in particular relates to a two-dimensional copper carbide electrode material and a method for calculating its lithium storage performance. Background Art

[0002] Rechargeable lithium-ion batteries (LIBs) have become an indispensable and important component of modern energy storage systems such as smartphones, electric vehicles, and power grids. With the rapid growth of demand in these fields, the performance requirements for lithium-ion batteries have also increased. Since the performance of lithium-ion batteries mainly depends on the quality of electrode materials, it has become an urgent task to develop electrode materials with better performance to achieve higher power and energy density in the full battery system.

[0003] Currently, graphite is a commonly used commercial negative electrode material in lithium-ion batteries. It has low lithium ion insertion chemical potential and cost-effectiveness; however, its low density of active sites per unit mass (theoretical capacity 372mAh / g) has made it difficult to meet the requirements of high energy density, and its ion diffusion rate is slow, which seriously limits its performance in situations requiring high power output. In order to overcome these shortcomings, researchers are exploring negative electrode materials with larger specific surface area and faster ion diffusion rate to achieve higher battery charge and discharge power and larger battery capacity.

[0004] Some two-dimensional materials, such as graphene, silicene, and two-dimensional transition metal compounds (MXenes), show the potential to replace traditional graphite due to their large surface-to-volume ratio and ion diffusion channels. Among these materials, carbon-based MXenes, such as , , , , has shown broad prospects as anode materials for LIBs.

[0005] Therefore, based on the first principles, we will conduct in-depth research on new materials in two dimensions. The possibility of (copper carbide) as anode material for lithium-ion batteries is of great significance. Summary of the invention

[0006] In order to overcome the deficiencies in the prior art, the present invention provides a two-dimensional copper carbide electrode material.

[0007] The second object of the present invention is to provide a method for calculating the lithium storage performance of the above-mentioned two-dimensional copper carbide electrode material.

[0008] The technical solution of the present invention to solve the above technical problems is:

[0009] A two-dimensional copper carbide electrode material comprises a C atomic layer in the middle and Cu atomic layers on both sides of the C atomic layer, wherein the C atomic layer and the two Cu atomic layers are connected via a Cu-C-Cu bond.

[0010] In a preferred embodiment of the present invention, the lattice constants a and b of the two-dimensional copper carbide electrode material are equal and are both 3.048Å.

[0011] In a preferred embodiment of the present invention, the Cu-C bond length in the two-dimensional copper carbide electrode material is 2.008Å.

[0012] In a preferred embodiment of the present invention, the space group of the two-dimensional copper carbide electrode material is P-3m1.

[0013] A method for calculating the lithium storage performance of a two-dimensional copper carbide electrode material comprises the following steps:

[0014] Step 1: Derive the crystal structure of two-dimensional transition metal compounds from the crystal structure database The basic structure of the Cu atom was replaced by VESTA software The position of the Mn atoms in the two-dimensional infrastructure;

[0015] Step 2: The VASP simulation software package based on density functional theory is used for first-principles calculations. During the calculation process, the PBE exchange-correlation function is used based on the generalized gradient approximation;

[0016] Step 3: Set relevant parameters for two-dimensional The basic structure is optimized to obtain a two-dimensional Optimized structure;

[0017] Step 4: 2D The optimized structure is subjected to static calculation and electronic property calculation to obtain the two-dimensional The energy band diagram of

[0018] Step 5: Use VESTA software to capture a 6×6×1 two-dimensional The supercell was calculated using the VASP simulation software package. The phonon spectrum of

[0019] Step 6: Use VESTA software to intercept 3×3×1 two-dimensional Supercell, add lithium ions for adsorption calculation;

[0020] Step 7: Use the climbing image forced elastic band method CI-NEB to search for lithium ions in two dimensions The optimal diffusion path from one adsorption point to another on the surface, and the diffusion barrier is calculated;

[0021] Step 8: Gradually add lithium ions to calculate and obtain a 3×3×1 two-dimensional The maximum number of lithium ions adsorbed by the supercell is calculated and the two-dimensional storage capacity of lithium.

[0022] In a preferred embodiment of the present invention, in step 3, the relevant parameters are set as follows: the mechanical convergence standard is 0.01 eV / A, the energy convergence threshold is 10-5 eV, and the plane wave cutoff energy is 600 eV.

[0023] In a preferred embodiment of the present invention, in step 7, the calculated diffusion barrier is 0.075 eV.

[0024] In a preferred embodiment of the present invention, in step 8, a 3×3×1 two-dimensional The maximum number of lithium ions adsorbed by the supercell is 36.

[0025] In a preferred embodiment of the present invention, in step 8, the two-dimensional Storage capacity of lithium:

[0026] ;

[0027] Where: n is the number of adsorbed ions, F is the Faraday constant, which is 26801mA.h / mol; M is the two-dimensional The molar mass of the supercell.

[0028] In a preferred embodiment of the present invention, in step 8, the two-dimensional The storage lithium capacity is 770.7 mAh / g.

[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0030] 1. The two-dimensional copper carbide electrode material of the present invention not only has excellent structural stability and electrical conductivity, but also can effectively adsorb lithium ions, and the migration barrier of lithium ions on its surface is only 0.075 eV. This low barrier value indicates that the two-dimensional copper carbide electrode material of the present invention has excellent structural stability and electrical conductivity, and can effectively adsorb lithium ions. The electrode material has an extremely high charge and discharge speed in the battery.

[0031] 2. The theoretical specific capacity of the two-dimensional copper carbide electrode material of the present invention is as high as 770.7 mA h / g, which is much better than 372 mAh / g of graphite. This further confirms that the two-dimensional copper carbide electrode material of the present invention has a high specific capacity of 770.7 mA h / g, which is much better than 372 mAh / g of graphite. The electrode material has superior performance as an electrode material for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a top view of a 3×3 supercell of the two-dimensional copper carbide electrode material of the present invention.

[0033] Figure 2 This is a side view of a 3×3 supercell of the two-dimensional copper carbide electrode material of the present invention.

[0034] Figure 3 Two-dimensional The phonon spectrum.

[0035] Figure 4 Two-dimensional Energy band diagram of .

[0036] Figure 5 Two-dimensional Schematic diagram of the sites for lithium ion adsorption.

[0037] Figure 6 This is the minimum energy diffusion path diagram of lithium ions.

[0038] Figure 7 Schematic diagram of the minimum diffusion barrier.

[0039] Figure 8 Two-dimensional Top view of the adsorption of two layers of lithium ions.

[0040] Fig. 9 Two-dimensional Side view of the adsorption of two layers of lithium ions. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0042] See also Figure 1-Figure 9 The two-dimensional copper carbide electrode material of the present invention comprises a C atomic layer in the middle and Cu atomic layers on both sides of the C atomic layer; the C atomic layer and the two Cu atomic layers are connected by Cu-C-Cu bonds; the two-dimensional The lattice constants a and b of the electrode material are equal and are both 3.048Å; The Cu-C bond length in the electrode material is 2.008Å and the space group is P-3m1.

[0043] In phonon dispersion analysis, the presence of positive frequencies is a sign of the dynamic stability of the system, while the presence of negative frequencies suggests that the structure may be unstable. The phonon dispersion along the Γ-MK-Γ path is analyzed as Figure 3 The results show that no negative frequencies appear in any case, which confirms the two-dimensional dynamic stability.

[0044] In addition, the conductivity of electrode materials is also crucial to their electrochemical performance. The band structure of Figure 4 As shown in the figure, the vertical coordinate 0 is the Fermi level. The energy band diagram shows that its band gap width is zero, showing a metal band structure, which indicates that the two-dimensional Has excellent electrical conductivity.

[0045] In addition, by calculating the lithium ion in two dimensions The diffusion barrier on the surface, where the minimum energy diffusion path is Figure 6 As shown, the diffusion barrier is Figure 7 As shown in Figure 2, the diffusion barrier is 0.075 eV, which is lower than that of other two-dimensional materials (e.g. 0.43eV, 0.24eV) is smaller than that of the two-dimensional It is conducive to the diffusion of lithium ions, so it will have high input and output power when used as a lithium battery electrode material.

[0046] Since lithium ions are adsorbed layer by layer on a two-dimensional Above, and two-dimensional It is symmetrical about the center from top to bottom, so the first layer at position 1 adsorbs 9 lithium ions on the upper and lower sides respectively, and the second layer also adsorbs 9 lithium ions respectively, such as Figure 8 and Fig. 9 As shown, the first layer adsorption height is 2.091Å; the second layer adsorption height is 4.389Å.

[0047] See also Figure 1-Figure 9 The method for calculating the lithium storage performance of the two-dimensional copper carbide electrode material of the present invention comprises the following steps:

[0048] Step 1: Derive the structure of two-dimensional transition metal compounds (MXenes) from the existing public crystal structure database The basic structure of the Cu atom was replaced by VESTA software The position of the Mn atoms in the two-dimensional infrastructure;

[0049] Step 2: The VASP simulation software package based on density functional theory was used for first-principles calculations. During the calculation process, the PBE exchange-correlation function was used based on the generalized gradient approximation (GGA).

[0050] Step 3: Set the mechanical convergence standard to 0.01eV / A, the energy convergence threshold to 10-5eV, and the plane wave cutoff energy to 600eV; The basic structure is optimized to obtain a two-dimensional The optimized structure (such as Figure 1 and Figure 2 shown);

[0051] Step 4: 2D The optimized structure is subjected to static calculation and electronic property calculation to obtain the two-dimensional The energy band diagram (such as Figure 4 The energy band diagram shows a two-dimensional The bandgap width is zero, showing a metallic band structure, which indicates that the two-dimensional Has excellent electrical conductivity;

[0052] Step 5: Use VESTA software to capture a 6×6×1 two-dimensional The supercell was calculated using the VASP simulation software package. The phonon spectrum (such as Figure 3 As shown); Since the phonon spectrum has no imaginary frequency, it proves that the two-dimensional The structure is stable;

[0053] Step 6: In order to reduce the impact of marginal effects, VESTA software was used to intercept a 3×3×1 two-dimensional Supercell, adding lithium ions for adsorption calculation; due to the periodicity of the material, the two-dimensional All possible adsorption sites (such as Figure 5 As shown), the stable adsorption point is position 1, and the adsorption energy is -1.826 eV;

[0054] Step 7: Use the climbing image forced elastic band method CI-NEB (Climbing Image Nudged ElasticBand) to search for lithium ions in two dimensions The optimal diffusion path from one adsorption site to another on the surface (e.g. Figure 6 As shown, and the diffusion barrier is obtained by calculation (as Figure 7 As shown), where the calculated diffusion barrier is 0.075 eV;

[0055] Step 8: Gradually add lithium ions to calculate and obtain a 3×3×1 two-dimensional The maximum number of lithium ions adsorbed by the supercell is 36 (such as Figure 8 and Fig. 9 As shown in the figure), that is, two layers of lithium ions are adsorbed on the upper and lower sides; the two-dimensional Storage capacity of lithium:

[0056] ;

[0057] Where: n is the number of adsorbed ions, F is the Faraday constant, which is 26801mA.h / mol; M is the two-dimensional The molar mass of the supercell; in this embodiment, the two-dimensional The storage lithium capacity is 770.7 mAh / g.

[0058] In summary, the two-dimensional copper carbide electrode material of the present invention not only has excellent structural stability and conductive properties, but also can effectively adsorb lithium ions, and the migration barrier of lithium ions on its surface is only 0.075 eV. This low barrier value indicates that the two-dimensional copper carbide electrode material of the present invention has extremely high charging and discharging speeds in the battery; in addition, the theoretical specific capacity of the two-dimensional copper carbide electrode material of the present invention is as high as 770.7 mA h / g, which is much better than 372 mAh / g of graphite, which further confirms the superior performance of the two-dimensional copper carbide electrode material of the present invention as an electrode material for lithium ion batteries.

[0059] The above is a preferred embodiment of the present invention, but the embodiment of the present invention is not limited to the above content. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A two-dimensional copper carbide electrode material, characterized in that: It includes a C atomic layer in the middle and Cu atomic layers on both sides of the C atomic layer, wherein the C atomic layer and the two Cu atomic layers are connected via Cu-C-Cu bonds.

2. The two-dimensional copper carbide electrode material according to claim 1, characterized in that: The lattice constants a and b of the two-dimensional copper carbide electrode material are equal and are both 3.048Å.

3. The two-dimensional copper carbide electrode material according to claim 2, characterized in that: The Cu-C bond length in the two-dimensional copper carbide electrode material is 2.008Å.

4. The two-dimensional copper carbide electrode material according to claim 1, characterized in that: The space group of the two-dimensional copper carbide electrode material is P-3m1.

5. A method for calculating the lithium storage performance of the two-dimensional copper carbide electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Derive the crystal structure of two-dimensional transition metal compounds from the crystal structure database The basic structure of the Cu atom was replaced by VESTA software The position of the Mn atoms in the two-dimensional infrastructure; Step 2: The VASP simulation software package based on density functional theory is used for first-principles calculations. During the calculation process, the PBE exchange-correlation function is used based on the generalized gradient approximation; Step 3: Set relevant parameters for two-dimensional The basic structure is optimized to obtain a two-dimensional Optimized structure; Step 4: 2D The optimized structure is subjected to static calculation and electronic property calculation to obtain the two-dimensional The energy band diagram of Step 5: Use VESTA software to capture a 6×6×1 two-dimensional The supercell was calculated using the VASP simulation software package. The phonon spectrum of Step 6: Use VESTA software to intercept 3×3×1 two-dimensional Supercell, add lithium ions for adsorption calculation; Step 7: Use the climbing image forced elastic band method CI-NEB to search for lithium ions in two dimensions The optimal diffusion path from one adsorption point to another on the surface, and the diffusion barrier is calculated; Step 8: Gradually add lithium ions to calculate and obtain a 3×3×1 two-dimensional The maximum number of lithium ions adsorbed by the supercell is calculated and the two-dimensional storage capacity of lithium.

6. The method for calculating the lithium storage performance of the two-dimensional copper carbide electrode material according to claim 5, characterized in that: In step 3, the relevant parameters are set as follows: the mechanical convergence standard is 0.01 eV / A, the energy convergence threshold is 10-5 eV, and the plane wave cutoff energy is 600 eV.

7. The method for calculating the lithium storage performance of the two-dimensional copper carbide electrode material according to claim 5, characterized in that: In step 7, the diffusion barrier is calculated to be 0.075 eV.

8. The method for calculating the lithium storage performance of the two-dimensional copper carbide electrode material according to claim 5, characterized in that: In step 8, the 3×3×1 two-dimensional The maximum number of lithium ions adsorbed by the supercell is 36.

9. The method for calculating the lithium storage performance of the two-dimensional copper carbide electrode material according to claim 5, characterized in that: In step 8, the two-dimensional Storage capacity of lithium: ; Where: n is the number of adsorbed ions, F is the Faraday constant, which is 26801mA.h / mol; M is the two-dimensional The molar mass of the supercell.

10. The method for calculating the lithium storage performance of the two-dimensional copper carbide electrode material according to claim 9, characterized in that: In step 8, the two-dimensional The storage lithium capacity is 770.7 mAh / g.

Citation Information

Patent Citations

  • Methods and apparatuses for production of carbon, carbide electrodes, and carbon compositions

    CN107108215A

  • Application of carbon material and analog simulation method thereof

    CN113036123A